Factors affecting value industrial sector manufacturing companies registered consumption items on bei from 2018 to 2020 - Fortuna, Sandra; Zulfikar, Zulfikar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this study is to investigate how business value is impacted by sound corporate governance, profitability, managerial ownership, institutional ownership, and firm size. A manufacturing firm in the consumer products industry is the focus of this study. The methodology used in this study is quantitative. The use of study variables to test hypotheses is emphasized in the quantitative technique of research. The secondary data used in this study came from the IDX-published summary of the yearly financial statements' outcomes. 43 manufacturing enterprises were chosen as the sample for this study using the purposive sampling method. Multiple linear regression analysis is the statistical technique used to assess statistical hypotheses. According to the study's findings, only one of the two hypotheses was confirmed, and the other was disproved. This study finds that management ownership, profitability, strong corporate governance, and business size have little bearing on the value of a firm, while institutional ownership affects firm value.